Modeling Analysis, Findings, Development, Organizing the Material and Learning for Students in Islamic Boarding Schools - Apdoludin Apdoludin; Martinisyamin Martinisyamin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
This study aims to determine the effect of a learning model called AFDOL (Analyzing, Finding, Developing, Organizing, and Learning (AFDOL) to increase students' critical thinking skills to find and gain new knowledge in learning Islamic traditional book at pesantren. This research is an R&D. It was carried out in class XII at pesantren in Jambi City. Two parallel classes were used, one class serving as the control group and one class as the experimental group. The result shows that AFDOL learning model can further improve students' critical thinking skills compared to conventional learning models. The learning model can improve students’ critical thinking skills to find new knowledge in learning Islamic traditional books. It enables teachers to deliver a more systematic learning process to improve students' understanding and critical thinking skills in learning Islamic traditional books.